Understanding institutions: different paradigms, different conclusions (Revista de Administração, 2017)
There is widespread agreement across the social sciences that institutions matter. Although there is widespread agreement that institutions shape the behavior of actors, there are disagreements over the extent to which they actually influence individuals and the degree to which people can shape them. This article argues that these disagreements derive from the fact that scholars are studying different institutions at different levels. Many misunderstandings within the social sciences result from the failure to understand that scholars are often studying different phenomena. This problem would appear to be particularly stark in the discipline of Business Administration because it draws on a variety of areas of study in the social sciences.